THE DIALECTICAL UNITY OF HARD AND SOFT SKILLS IN THE EDUCATIONAL ENVIRONMENT OF HIGHER EDUCATION DEPARTMENTS - Zvyagolska, I.M.; Polyanska, V.P.; Derevyanko, T.V. (Актуальні проблеми сучасної медицини: Вісник Української медичної стоматологічної академії, 2025)
Relevance. Modern educational trends open up wide opportunities for educators, allowing them to focus on improving the quality of professional training of students at all levels. This is crucial for achieving the multifaceted goals set out in the modern mission of universities. Thanks to close cooperation between educators and students, a new generation of specialists is being formed who have the knowledge and skills to meet the needs of the modern labor market. This, in turn, contributes to the positive development of the world economy. Objectives. The article highlights the issue of one of the important areas in the training of new generation of specialists, who in their practical activities organically combine professional and superprofessional skills and abilities (hard skills and soft skills). Materials and methods. Through the use of theoretical research methods and contextual analysis of contemporary scientific and informational sources, the authors identified key categories of supra-professional (universal) skills and competencies encompassed by the concept of Soft Skills. Integrating these skills into the educational environment of university departments broadens the potential for developing essential personal qualities in higher education applicants. Results. The effective pedagogical approaches employed by faculty at the Department of Microbiology, Virology, and Immunology of Poltava State Medical University and the Department of Biology, Human Health, and Physical Rehabilitation of V.G. Korolenko Poltava National Pedagogical University facilitated a dialectical integration of hard skills and soft skills during the educational and cognitive process. According to the outcomes of control assessments, this integration significantly enhanced both the professional competencies and personal attributes of students enrolled in the respective educational and professional programs. Given these results, the described approach may be effectively adopted by other departments within higher education institutions.